Pengaruh Tekanan Eksternal, KetidakpastianLingkungan Dankomitmen Manajemen Terhadap Penerapan TransparansiPelaporan Keuangan(Studiempirispada Skpd Kabupatenkebumen) - Fitrianto, Fahmi Fakih; , Drs. Suyatmin Waskito Adi, M.Si (2016)
This research has the purpose to analyze the influence of external pressures environmental uncertainty and management commitment towards the implementation of the transparency of financial reporting. The population in this research is all employees or employees who work on a work Device Unit (SKPD) Areain in district of Kebumen. Sample collection method by using purposive sampling technique. The samples used in the study totalled 72 respondents. In this study to analyze the data using multiple regression analyze. Research results show that R2 values obtained 0.438 43.8% which meant that the application of the transparency of financial reporting was influenced by external pressures, environmental uncertainty and commitment manajmen. Rest as much as 56.2% influenced by variables outside of the model. The t-test results showed that the external pressure, the uncertainty of the environment and management's commitmentto the implementation of the transparency of financial reporting. Keywords: financial transparency, environtmentl uncertainty, external pressure and commiment management.